Bereaved parents’ experiences of research participation - Butler, Ashleigh E.; Hall, Helen; Copnell, Beverley (BMC palliative care, 2018)
As understandings of the impacts of end-of-life experiences on parents' grief and bereavement increase, so too does the inclusion of bereaved parents into research studies exploring these experiences. However, designing and obtaining approval for these studies can be difficult, as guidance derived from bereaved parents' experiences of the research process are limited within the current literature. We aimed to explore bereaved parents' experiences of research participation in a larger grounded theory study exploring experiences of the death of a child in the paediatric intensive care unit. Data were obtained during follow-up phone calls made to 19 bereaved parents, five of whom provided data from their spouse, 1 week after their participation in the study. Participants were asked to reflect on their experiences of research participation, with a focus on recruitment methods, timing of research contact, and the location of their interview. Parents' responses were analysed using descriptive content analysis. Our findings demonstrate that despite being emotionally difficult, parents' overall experiences of research participation were positive. Parents preferred to be contacted initially via a letter, with an opt in approach viewed most favourably. Most commonly, participants preferred that research contact occurred within 12-24 months after their child's death, with some suggesting contact after 6 months was also appropriate. Parents also preferred research interviews conducted in their own homes, though flexibility and parental choice was crucial. Findings from this study offer further insight to researchers and research review committees, to help ensure that future studies are conducted in a way that best meets the unique needs of bereaved parents participating in research.